2018
DOI: 10.1002/anie.201811896
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Regio‐ and Stereoselective Hetero‐[5+2] Cycloaddition of Oxidopyrylium Ylides and Cyclic Imines

Abstract: We have developed the first intermolecular hetero-[5+ +2] cycloaddition reaction between oxidopyrylium ylides and cyclic imines with excellent control of regio-and stereoselectivity.S urprisingly,d ivergent stereochemistry was observed depending on the substitution pattern of the oxidopyrylium ylide.T his new reaction provides quicka ccess to highly substituted nitrogen-containing seven-membered rings-azepanes.N otably,abroad range of oxidopyrylium ylides and cyclic imines participate in this novel hetero-[5+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The corresponding cycloadduct 4ak was exclusively obtained in 31% yield when ethyl propiolate was used as the alkyne dipolarophile. The reaction with dihydroisoquinoline produced endo - 4al in 26% yield . The yields of 4ak and endo - 4al were improved (46 and 34%, respectively) using the slow addition technique.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding cycloadduct 4ak was exclusively obtained in 31% yield when ethyl propiolate was used as the alkyne dipolarophile. The reaction with dihydroisoquinoline produced endo - 4al in 26% yield . The yields of 4ak and endo - 4al were improved (46 and 34%, respectively) using the slow addition technique.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrylium salts have been used as synthetic intermediates in organic chemistry, especially serving as either C4 or C5 units in [4 + 2], [5 + 1], and [5 + 2] cycloadditions. Although such strong electrophiles have been found to react readily with carbenes and α-carbonyl carbenoids showing the usual 1,1-dipolar reactivity, ,, we found that 2,6-disubstituted pyrylium salts underwent an unprecedented (3 + 2) annulation with the KRAs from benzils, leading to facile concurrent formation of both fully substituted furan rings and the challenging cis α,β-unsaturated carbonyl motifs . Herein, pyrylium ions formally serve as highly electrophilic C2 synthons bearing a Z -enone unit, whereas the KRAs derived from benzils function as C3 synthons for the first time.…”
mentioning
confidence: 87%
“…As potential carriers for hydrogen bonds, oxonium ylides provide intramolecular charge balance potentially involving hydrogen bonds, which set the stage for the investigation of new transformations and mechanisms. [7][8][9][10] For example, oxonium ylide intermediates with static hydrogen bonds are likely responsible for the metal carbenoid O-H insertion, reported by Yu's 11 and Fang's 12 group through DFT calculations.…”
Section: Introductionmentioning
confidence: 99%